2014
DOI: 10.1515/epoly-2014-0071
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PMMA/AB nanofiber composites for hydrogen storage applications

Abstract: In this work, poly(methyl methacrylate) (PMMA)/ammonia borane (AB) nanofiber composites were fabricated and the synergetic nanoconfinement effect of nanofibers on dehydrogenation temperature and the removal of unwanted by-products of AB (NH3 BH3) were studied. The results of the dehydrogenation of PMMA/AB samples showed an exothermic reaction temperature of 112°C, which is significantly lower than that of pure AB (120°C). Furthermore, the interaction between AB molecules and PMMA nanofiber structures decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The ammonia borane nanophase was in the form of 4-nm nanoparticles, and released pure hydrogen from 50 • C. A last synthetic approach is nanostructuration by electrospinning, where nanofibers of a polymer encapsulating ammonia borane are elaborated. Useful polymers for that purpose are polystyrene [284], polyvinylpyrrolidone [285], poly(methyl methacrylate) [286], polyethylene oxide [287] and polyacrylamide [288]. In each case, embedded ammonia borane nanophase showed improved dehydrogenation properties in comparison with the bulk counterpart, but the release of some ammonia, diborane and/or borazine could not be avoided.…”
Section: Nanoconfinement Of Ammonia Boranementioning
confidence: 99%
“…The ammonia borane nanophase was in the form of 4-nm nanoparticles, and released pure hydrogen from 50 • C. A last synthetic approach is nanostructuration by electrospinning, where nanofibers of a polymer encapsulating ammonia borane are elaborated. Useful polymers for that purpose are polystyrene [284], polyvinylpyrrolidone [285], poly(methyl methacrylate) [286], polyethylene oxide [287] and polyacrylamide [288]. In each case, embedded ammonia borane nanophase showed improved dehydrogenation properties in comparison with the bulk counterpart, but the release of some ammonia, diborane and/or borazine could not be avoided.…”
Section: Nanoconfinement Of Ammonia Boranementioning
confidence: 99%
“…The PCL channel which provides a barrier between the healing nerve and surrounding media was fabricated from nanofibers with relatively non-uniform distribution. Previous studies revealed that the electrospun solution condition (including viscosity, charge density and shear stress) and solvent vapor pressure can simultaneously affect the fiber diameter distribution [ 52 ]. Another parameter which can affect fiber distribution is collector rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The FESEM images of (PVA+CS)+ZnO NPs electro-spun fibers at different magnifications are shown in Figure 3. The fibers presented a smooth surface compared to the polymer fibers without nanoparticles, average diameter of PVA/CTS/ZnO NP fibers was 100.8 nm, more significant than the average diameter of the polymer fibers without nanoparticles Figure 3A there for when the nanofiber diameter increased by increasing the weight concentration of NP because agglomeration of nanoparticles [23].…”
Section: Morphological and Microstructural Analysismentioning
confidence: 90%
“…Favorable mechanical properties, whereas added 0.4, 0.6 ZnO nanoparticles tend to cluster inside the (PVA+CS) matrix due to these aggregated nanoparticles acting as stress concentration sites. Moreover, the aggregated nanoparticles hinder the (PVA+CS) chains' mobility, which lowers the nano composites' elongation at the break, for a high concentration of ZnO reduced mechanical properties [23]. 5, displays the Hardness results.…”
Section: Nanoindentation Analysis Of the Samplesmentioning
confidence: 99%